Impacto económico de la COVID-19 en la rentabilidad de las pymes en la provincia de Trujillo 2019 - 2021 - Cabrera Aguilar, Gustavo Gonzalo (2022)
The general objective of this research was to determine the economic impact of COVID-19 on the profitability of SMEs in the province of Trujillo, 2019 - 2021. The type of research was applied, the approach was quantitative, the scope was descriptive and the research design is non-experimental. The type of research is applied, quantitative approach, descriptive scope and non-experimental design. As a result, the social government measures affected the profitability of the companies mainly due to mandatory social isolation, the economic government measures did affect the profitability of the companies, mainly due to the Reactiva Peru Program. In the footwear sector, its net profit in 2020 was reduced by 1.81%, ROA by 7.96% and ROE by 5.68%, the gastronomic sector is one of the most affected by the pandemic since its ROE went from 9.72% to -10.41% in the middle of the pandemic. The main conclusion is that Covid-19 has a positive impact on companies in the pharmaceutical and transport sectors; but it had a negative impact on companies in the footwear, construction and gastronomic sectors, the latter being the most affected.